Comparative Analysis of Electromyographic Indicators of Subjects during Sensorimotor Training in Various Social Conditions of Activity in Dyads - Galushka, E. S.; Murtazina, E. P.; Pertsov, S. S. (Journal of evolutionary biochemistry and physiology, 2025)
The aim of this work is to analyze the amplitude-spectral indices of electromyograms and their correlations with the performance of subjects during sensorimotor training in different social conditions of activity in dyads. The study was carried out on 256 subjects. As a model of activity, the sensorimotor training “Columns” of the software and hardware complex “BOS-Kinesis” (LTD “Neurotech”, Taganrog) was used with biological feedback from electromyographic signals from the radial flexor of the wrist ( flexor carpi radialis ) of the leading hand of the subjects performing the task in 3 social contexts: individual, competitive and cooperative. As a result of the study of EMG characteristics of the sensorimotor activity of subjects in different social conditions, the following gender differences were revealed: at the individual stage, women have higher frequency characteristics of EMG, and men have higher amplitude and power of the EMG spectrum at the stages of competition and cooperation. The dynamics of EMG characteristics in women, unlike men, is associated with changes in social activity conditions. The variability of the frequency characteristics of the EMG spectrum increased in both men and women under joint activity conditions. Opposite directions of changes in the variability of the integral amplitude and total power of the EMG spectrum in joint activity contexts compared to individual ones were found: an increase in these indicators in men, but a decrease in women. In the woman sample, the training performance correlated positively with the average EMG frequency values in all activity contexts, and negatively with the amplitude and power of the EMG spectrum during cooperation. The performance of men and women in all sensorimotor activity conditions correlated negatively with the variability of EMG characteristics. The results of the study contribute to the understanding of the features of the implementation of voluntary human movements when performing sensorimotor tasks in various conditions of social interactions. The obtained data can form the basis for identifying prognostic criteria for the effectiveness of joint sensorimotor activity to create methods for selecting successful teams and optimizing production processes.